2014
DOI: 10.1371/journal.pone.0094109
|View full text |Cite
|
Sign up to set email alerts
|

Underperformance of African Protected Area Networks and the Case for New Conservation Models: Insights from Zambia

Abstract: Many African protected areas (PAs) are not functioning effectively. We reviewed the performance of Zambia’s PA network and provide insights into how their effectiveness might be improved. Zambia’s PAs are under-performing in ecological, economic and social terms. Reasons include: a) rapidly expanding human populations, poverty and open-access systems in Game Management Areas (GMAs) resulting in widespread bushmeat poaching and habitat encroachment; b) underfunding of the Zambia Wildlife Authority (ZAWA) result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 33 publications
1
118
0
2
Order By: Relevance
“…Based on Zambia's wildlife legislation, illegal killing and trafficking of elephants attract penalties not less than 5 years and 7 years respectively and not exceeding a term of imprisonment of 20 years and 25 years respectively, without the option of a fine. Law enforcement efforts are undermined by funding shortages for protected area management (Lindsey et al 2014), and by low salaries for law enforcement officers, which makes them vulnerable to being coerced into assisting ivory traders. Such factors may compromise the effectiveness of enforcement systems designed to save charismatic species (Bennett, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Zambia's wildlife legislation, illegal killing and trafficking of elephants attract penalties not less than 5 years and 7 years respectively and not exceeding a term of imprisonment of 20 years and 25 years respectively, without the option of a fine. Law enforcement efforts are undermined by funding shortages for protected area management (Lindsey et al 2014), and by low salaries for law enforcement officers, which makes them vulnerable to being coerced into assisting ivory traders. Such factors may compromise the effectiveness of enforcement systems designed to save charismatic species (Bennett, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the national parks, this would require elevated funding for Zambia Wildlife Authority (ZAWA) or co-management through partnerships between ZAWA, Non-Governmental Organisations and private sector. Wildlife populations in protected areas in Zambia with co-management agreements in place appear to be faring better than in parks without such support (Lindsey et al 2014). There is currently co-management in place for North Luangwa and Lower Zambezi National Parks, and support is provided to ZAWA for law enforcement by an NGO in South Luangwa National Park.…”
Section: Discussionmentioning
confidence: 99%
“…2013, 2014; Lindsey et al. 2014). The effects of anthropogenic activities on protected leopard populations have been investigated in several ecosystems across their distribution (Balme et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that while African protected areas have generally been successful in maintaining habitats, they have been less successful in mitigating the effect of human-induced declines in large mammal populations (Craigie et al 2010;Geldman et al 2013;Lindsey et al 2014). The improvement of protected areas networks, for example through the enforcement of private property rights, is crucial to ensure the sustainability of species populations.…”
Section: Discussionmentioning
confidence: 99%